The Kotayk Survey Project (KSP): an overview of the first six years of activities (2013-2018) - Petrosyan, Artur; Dan, Roberto; Vitolo, Priscilla; Melikyan, Varduhy; Moradi, Ghasem; Zecchi, Chiara; Saccone, Tommaso (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
The Kotayk Survey Project is an Armenian–Italian expedition aimed at the archaeological study of Kotayk Region, Armenia. The research project is developed under a Memorandum of Understanding signed between Institute of Archaeology and Ethnography of National Academy of the Sciences of the Republic of Armenia (IAE NAS RA) and ISMEO – International Association of Mediterranean and Oriental Studies. The project is co-funded by ISMEO, IAE NAS RA and MAECI (Ministry of Foreign Affairs and International Cooperation of Italy). The project combines an extensive survey in the region, the subsequent selection of important sites for test trenches, and a major excavation in the Urartian fortress of Solak-1/Varsak. The activities started in 2013 with a preliminary analysis of the territory through the study of satellite images of the area, followed by a field survey over an extensive area, which covers about 100,000 ha. During the survey activities, 114 archaeological sites have been identified, spanning from Palaeolithic to Late Medieval. The research is still in progress with two main aims: on one side the excavation, conservation and touristic fruition of the Urartian fortress of Solak-1/Varsak, and on the other, the creation of archaeological maps of the region, that will illuminate the massively exploited and partially still unknown area of Kotayk Region. The work of the Kotayk Survey Project is part of a long tradition of cooperation between Armenian and Italian archaeological institutions and develops from the history of prior investigations in the region, that first recognised the important heritage of this territory.